Transformasi Strategi Komunikasi Pemasaran di Era Digital: Studi Kasus pada Komunitas Pedagang Multi-Etnis di Kota Cirebon - Fauzi, Rifqi; Chaerowati, Dede (Interaction Communication Studies Journal, 2025)
This study aims to explore how multiethnic merchant communities in Cirebon City adapt to digital technologies within their marketing communication strategies, thereby generating a holistic understanding of authentic and sustainable transformation mechanisms. Employing a qualitative approach with an intrinsic case study design, the research involved in-depth interviews, participant observation, and document analysis with eighteen informants from diverse ethnic backgrounds over a six-month period.The findings indicate that transformation is not merely a technical substitution, but rather a complex negotiation between cultural heritage and the demands of modernity, unfolding through four distinct phases of change with an average duration of twenty-four weeks. The role of younger generations as facilitators of knowledge transfer, platform preferences aligned with local communication patterns, and cultural dimensions functioning as sources of competitive advantage emerge as critical insights. The study recommends the development of culturally sensitive digital literacy programs, localized policies that support digital transitions for traditional merchants, and communication strategies that integrate local cultural values with modern technological capabilities.